Evaluation factors for testing and validation of Clinical Reporting System - Sharma, Meenakshi; Aggarwal, Himanshu (International Journal of Computer Sciences and Engineering, 2025)
Automate Clinical decision support system(CRS) provide assistance to physician as well as to society to enhance quality of healthcare. Methodical and apposite testing a of automate reporting system prior to liberate to end-users is kind of critical aspect any automate expert system related to healthcare domain. Testing and validation, is one of the most vital and critical step of CRS because lack of well defined testing tools , oversight this step may lead to dangerous and severe outcome issues. Great efforts are required for testing of system as data collecting form number of resources and may be in different formats. Clinic data available in Electronic Health Records (EHR) form. Testing of such huge amount of clinical data by human became to tedious and risky because chances of mistakes are there. Adaption rate of clinical reporting system quite slow, as many of them not tested properly prior to liberate .Testing and Validation of CRS depends on various factors that considered in this paper. For testing technique, considered functional and structural techniques by receiving information for input from every level of progress.